Chemostratigraphy of Two Wells in Niger Delta Basin: An Integrated Approach to Stratigraphic Study - Itiowe*, Kiamuke; Adebayo Lucas, Frank; Ugwueze, Charles Ugwu; Lawson-Jack, Osaki (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Chemostratigraphic characterization and correlation was carried out on two wells in the Niger Delta with the aim to integrate chemostratigraphic data with already existing biostratigraphic information from the Niger Delta. Shale cutting samples taken within the interval of interest from both wells were subjected to inorganic geochemical and mineralogical analysis using energy dispersive x-ray fluorescence spectrometry (ED-XRF) and x-ray diffractometry, respectively. The key elements used for chemostratigraphic characterization and correlation for both wells were Al2O3, K2O, Na2O and Fe2O3. Four geochemical packages and three geochemical boundaries at depths of 8265ft, 9120ft and 10080ft were identified in #3 well, while two geochemical packages and one geochemical boundary at 4500ft were identified in the Sahaiawei-1 well. The primary mineralogical controls on the elemental variations identified in both wells were clay minerals (kaolinite, illite/muscovite, and chlorite), plagioclase, microcline, jarosite and pyrite. In this study, chemostratigraphic data was integrated with already existing biostratigraphic information, enabling the establishment of some informal geochemical markers in the Northern Delta and Greater Ughelli depobelts. Our research results will improve on the inorganic geochemistry and chronostratigraphic charts of the Niger Delta, and it will in future facilitate seismic interpretation and the identification of the Niger Delta petroleum play elements. Keywords: geochemical characterization; elemental chemostratigraphy; geochemical boundaries; inorganic geochemistry; Niger Delta Bain *Corresponding author: E-mail: kiamukeitiowe@yahoo.com